2013
DOI: 10.1111/hdi.12053
|View full text |Cite
|
Sign up to set email alerts
|

Who may not benefit from continuous renal replacement therapy in acute kidney injury?

Abstract: This study aimed to identify factors that may predict early kidney recovery (less than 48 hours) or early death (within 48 hours) after initiating continuous renal replacement therapy (CRRT) in acute kidney injury (AKI) patients. This is a multicenter retrospective observational study of 14 Japanese Intensive care units (ICUs) in 12 tertiary hospitals. Consecutive adult patients with severe AKI requiring CRRT admitted to the participating ICUs in 2010 (n=343) were included. Patient characteristics, variables a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 28 publications
4
22
0
1
Order By: Relevance
“…Kawarazaki et al examined the predictive factors of early kidney recovery (within 48 h) after CRRT initiation in AKI patients in a multicenter retrospective observational study of 14 Japanese ICUs. In multivariable regression analysis, urine output (mL/h), duration between ICU admission and CRRT initiation (days), and the SOFA score were related to early kidney recovery (OR 1.02, 0.65, 0.87; 95 % confidence interval [13].…”
Section: Reviewmentioning
confidence: 99%
“…Kawarazaki et al examined the predictive factors of early kidney recovery (within 48 h) after CRRT initiation in AKI patients in a multicenter retrospective observational study of 14 Japanese ICUs. In multivariable regression analysis, urine output (mL/h), duration between ICU admission and CRRT initiation (days), and the SOFA score were related to early kidney recovery (OR 1.02, 0.65, 0.87; 95 % confidence interval [13].…”
Section: Reviewmentioning
confidence: 99%
“…Our literature search found three observational studies that identified predictors of the possibility to wean patients from blood purification to date. [226]. The comparison of an early recovery group (those who could discontinue CRRT within 48 h of initiation; n = 52) and a control group that excepted patients who died early (n = 239) revealed that the urine output upon CRRT initiation (mL/h) (OR 1.02, 95% CI 1.01-1.03), the SOFA score upon CRRT initiation (OR 0.87, 95% CI 0.78-0.96), and the time from ICU admission to CRRT initiation (in days) (OR 0.65, 95% CI 0.43-0.87) were significantly associated with early weaning from CRRT.…”
Section: Commentarymentioning
confidence: 99%
“…Kawarazaki et al stellten in ihrer retrospektiven japanischen Kohorte aus 12 Zentren eine Assoziation von neurologischen Erkrankungen mit einem frühen Tod nach Nierenersatztherapie bei ANV (6 % vs. 1 %; OR 9,64; 95%-KI: 1,22-92,95; p = 0,03) als unabhängigen Risikofaktor fest, wobei die geringe Anzahl von Patienten eine Interpretation der Daten erschwert (n = 2 Kontrollgruppe, n = 3 in der Early-deathGruppe; [35]). …”
Section: » Es Besteht Ein Erhöhtes Relatives Risiko Für Einen Schlagaunclassified